Development of financial services based on cryptocurrencies - Dzhereleiko, S.; Shevchenko, Maryna Mykolaivna; Nazarova, Tetiana (Чорноморський державний університет ім. Петра Могили, 2023)
Initially, this was due to the fact that cryptocurrencies provided users with the ability to perform transactions and store their assets with a certain level of anonymity and privacy. Later on, it became evident that the use of cryptocurrencies guarantees security, speed, and efficiency in transactions. Currently, cryptocurrencies not only provide access to basic financial services for individuals with limited access to traditional banking systems but also offer users the ability to engage in a wide range of financial operations with specific advantages. Consequently, the development directions of cryptocurrency-based financial services have garnered significant interest in economic science today. Research is aimed at the comprehensive identification and systematic characterization of the fundamental characteristics and directions of the development of cryptocurrency-based financial services. The research findings have demonstrated that the functionality of asset utilization on cryptocurrency exchanges is expanding. As a result, currently, such exchanges allow users to buy, sell, and trade cryptocurrencies, providing liquidity and the ability to exchange between different cryptocurrencies and traditional currencies. The functionality of asset utilization within cryptocurrency wallets is expanding by increasing options for the storage and management of cryptocurrency assets. The functionality of asset utilization within cryptocurrency payment gateways is expanding by creating opportunities for businesses and individual users to accept payments in cryptocurrencies and convert them into traditional currencies at the current exchange rate. The functionality of asset utilization within cryptocurrency-collateralized loans is expanding, with more services emerging that allow users to use their cryptocurrency assets as collateral to obtain loans. The functionality of decentralized financial services is also expanding. Smart contracts, programmable contracts, proof of validation, and other integrations with DeFi protocols transform each financial service into a smart network.

Швидкий розвиток фінансових послуг на основі криптовалют є тенденцією вітчизняних фінансів. Початково, це зумовлювалося тим, що криптовалюти надавали користувачам можливість здійснювати транзакції та зберігати свої активи з певним рівнем анонімності та приватності. Пізніше стало очевидним, що використання криптовалюти гарантує безпеку, швидкість, ефективність трансакцій. Наразі криптовалюти не лише відкривають доступ до базових фінансових послуг для людей з обмеженим доступом до традиційних банківських систем, але і надають користувачам можливість здійснювати широкий спектр фінансових операцій з певними перевагами. Відтак, напрямки розвитку фінансових послуг на основі криптовалюти представляють тепер великий інтерес в економіці. Відповідно до вищенаведеного, дослідження спрямоване на загальний аналіз та системну характеристику специфіки та напрямків розвитку фінансових послуг на основі криптовалюти. За результатами дослідження доведено, що розширюється функціональність використання активів на криптовалютних біржах. Як наслідок, наразі такі біржі дозволяють користувачам купувати, продавати та торгувати криптовалютами, а також забезпечують ліквідність та можливість обміну між різними криптовалютами та традиційними валютами. Розширюється функціональність використання активів у криптовалютних гаманцях коштом розширення опцій для операцій зі зберігання та керування криптовалютними активами. Розширюється функціональність використання активів у криптовалютних платіжних шлюзах, внаслідок формування можливостей підприємств та індивідуальних користувачів приймати платежі в криптовалюті та конвертувати її в традиційні валюти або фіатні гроші за поточним обмінним курсом. Розширюється функціональність використання активів у межах криптовалютних заставних позик, з'являється більше послуг, що дозволяють користувачам використовувати свої криптовалютні активи як заставу для отримання позики. Розширюється функціональність децентралізованих фінансових послуг. SMART-контракти, програмні розумні контракти та інші за їх інтеграції з DeFi протоколами перетворюють кожну фінансову послугу на розумну мережу.
Розвиток фінансових послуг на основі криптовалют
Keywords: cryptocurrency assets; smart contracts; cryptocurrency wallets; cryptocurrency exchanges; криптовалютні активи; смарт-контракти; криптовалютні гаманці; криптовалютні біржі